2021
DOI: 10.1111/jpi.12714
|View full text |Cite
|
Sign up to set email alerts
|

Changing color and intensity of LED lighting across the day impacts on circadian melatonin rhythms and sleep in healthy men

Abstract: We examined whether dynamically changing light across a scheduled 16-h waking day influences sleepiness, cognitive performance, visual comfort, melatonin secretion, and sleep under controlled laboratory conditions in healthy men. Fourteen participants underwent a 49-h laboratory protocol in a repeated-measures study design. They spent the first 5 hours in the evening under standard lighting, followed by an 8-h nocturnal sleep episode at habitual bedtimes. Thereafter, volunteers either woke up to static light o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 61 publications
2
30
1
Order By: Relevance
“…10,112 When measured across a divergent series of real-world or in-lab conditions, sparser patterns of ambient illumination (with lower zeitgeber strength) during the day also associate with later sleep initiation, less sleep pressure/slow-wave-sleep buildup under states of rest or sleep deprivation, more nighttime awakenings, worse perceptions of sleep quality, less circadian-robust sleep cycles, and increases in reported insomnia symptoms. [113][114][115][116][117][118][119][120][121][122][123][124][125][126] These results are consistent with seasonally oriented studies of participants stationed in Antarctica that quantified (1) more light-induced https://doi.org/10.2147/NSS.S251712…”
Section: The Protective Role Of Daytime Light Against Lansupporting
confidence: 73%
“…10,112 When measured across a divergent series of real-world or in-lab conditions, sparser patterns of ambient illumination (with lower zeitgeber strength) during the day also associate with later sleep initiation, less sleep pressure/slow-wave-sleep buildup under states of rest or sleep deprivation, more nighttime awakenings, worse perceptions of sleep quality, less circadian-robust sleep cycles, and increases in reported insomnia symptoms. [113][114][115][116][117][118][119][120][121][122][123][124][125][126] These results are consistent with seasonally oriented studies of participants stationed in Antarctica that quantified (1) more light-induced https://doi.org/10.2147/NSS.S251712…”
Section: The Protective Role Of Daytime Light Against Lansupporting
confidence: 73%
“…Under strictly controlled laboratory conditions, we examined whether dynamic light across the day influences cognitive performance, visual comfort, melatonin secretion, sleepiness, and sleep ( 67 ). Volunteers either woke up with static daylight LED (100 lx at the pillow and 4000 K, melEDI 69 lx) or with a dynamic daylight LED that changed CCT (2700–5000 K) and intensity (0–100 lx at the pillow, melEDI 0.4–76 lx) across the day (daylight here refers to the spectral characteristics of the Toshiba TRI-R LED).…”
Section: Lighting Concepts That Address Non-visual Effects Of Lightmentioning
confidence: 99%
“…Recent studies revealed that through an optimised smart lighting system energy costs of 17 to 60% [7] can be saved compared to traditional static lighting solutions [7,10,11]. Besides the aspect of saving energy, research is focusing on the implementation of dynamic patterns of light exposure [12], which vary the illumination or the correlated colour temperature (CCT) to support the circadian rhythm [13] or task-related performance [12]. The discovery of intrinsically photosensitive ganglion cells (ipRGCs) [14][15][16][17][18] made clear that besides the image-forming properties of colour and brightness perception [19], the composition of a light spectrum [20] can also affect the human alertness and cognitive performance [6,[21][22][23].…”
Section: Introductionmentioning
confidence: 99%